2019
DOI: 10.2147/idr.s213099
|View full text |Cite
|
Sign up to set email alerts
|

<p>Usefulness of serum D-dimer for preoperative diagnosis of infected nonunion after open reduction and internal fixation</p>

Abstract: Purpose Infected nonunion after open reduction internal fixation (ORIF) is a serious complication. The aim of this study was to evaluate the usefulness of serum D-dimer for preoperative diagnosis of infected nonunion. Patients and methods Patients undergoing debridement and external fixation for infected nonunion (n=32) and replacement of internal fixation due to aseptic failure (n=34) were enrolled and compared in this retrospective study. The optimum cutoff value of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Until now, numerous studies have evaluated the performances that brinogen, D-dimer and platelet indices play in diagnosis of PJI, and most of these studies proved that brinogen, D-dimer and platelet indices were associated with PJI [27-29, 18, 30, 31]. Previous studies have demonstrated that the diagnostic values of plasma brinogen and serum D-dimer for diagnosis infected nonunion were good and compared with plasma D-dimer, plasma brinogen had better performance in diagnosing infected nonunion, which was consistent with the ndings in this study [19,32]. Based on our data, plasma brinogen had the higher AUC (0.807) than plasma D-dimer (0.755).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Until now, numerous studies have evaluated the performances that brinogen, D-dimer and platelet indices play in diagnosis of PJI, and most of these studies proved that brinogen, D-dimer and platelet indices were associated with PJI [27-29, 18, 30, 31]. Previous studies have demonstrated that the diagnostic values of plasma brinogen and serum D-dimer for diagnosis infected nonunion were good and compared with plasma D-dimer, plasma brinogen had better performance in diagnosing infected nonunion, which was consistent with the ndings in this study [19,32]. Based on our data, plasma brinogen had the higher AUC (0.807) than plasma D-dimer (0.755).…”
Section: Discussionsupporting
confidence: 89%
“…Inspired by this, many scholars have focused on exploring the potential values of coagulation-related parameters for diagnosing orthopaedic infections and have obtained positive outcomes that brinogen, D-dimer and PC are useful in reaching or refuting the diagnosis of periprosthetic joint infection (PJI) [14][15][16][17][18]. Moreover, past studies have indicated that Ddimer and brinogen could be potential diagnostic markers for infected nonunion [19,20]. However, the sample sizes of the studies were not enough large and there is no related study about the accuracy of platelet indices including platelet count (PC), plateletcrit (PCT), mean platelet volume (MPV), platelet distribution width (PDW), and PC/MPV in diagnosing infected nonunion after ORIF.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that fibrinogen, D-dimer, and platelet indices are associated with PJI [ 18 , 27 31 ]. Previous studies have shown that plasma fibrinogen and serum D-dimer have good value for diagnosis of infected nonunion, with the former having significantly better diagnostic value [ 19 , 32 ]. This is consistent with our study, where the AUC of plasma fibrinogen (AUC 0.807) was larger than that of plasma D-dimer (AUC 0.755).…”
Section: Discussionmentioning
confidence: 99%
“…In the field of orthopedics, fibrinogen, D-dimer, and PC have been found to be useful for diagnosis of periprosthetic joint infection (PJI) [ 14 18 ]. Some studies have also indicated that D-dimer and fibrinogen could be potential diagnostic markers for infected nonunion [ 19 , 20 ]; however, the sample sizes of these studies were small. There has been no study so far on the accuracy of platelet indices—including PC, plateletcrit, mean platelet volume (MPV), platelet distribution width (PDW), and PC/MPV ratio—in the diagnosis of infected nonunion after ORIF.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, research topics and concepts also altered over the course of the years. With the introduction of the FRI consensus group, the term “fracture-related infection” became the standard, with more recent topics primarily focusing on risk factors and diagnostic criteria of FRI [ 15 , 40 43 ]. Prior to this, researchers focused on the treatment of FRI [ 44 46 ], with a focus on debridement, bone transfer, and antibiotic treatment.…”
Section: Discussionmentioning
confidence: 99%